SOCIAL CAPITAL FORMATION SEBAGAI STRATEGI PENGEMBANGAN KOMUNITAS BERBASIS ASET DALAM PEMBANGUNAN KEPARIWISATAAN (Studi Kasus Kepariwisataan di Labuan Bajo, Manggarai Barat, Nusa Tenggara Timur) - Tandikara, Willy; Zaka Lawang, Robert Markus (Jurnal Insani, 2018)
Currently tourism is considered to have a potential role as a driver of socio-economic development. The tourism sector has its own attractiveness, making it the choice for the perpetrators to get a better life gained through the multiplier effect in job opportunities, business opportunities and income distribution. However, studies that analyze the structures of capital owned by local communities in relation to the tourism industry and how the increase of capital through social capital in order to create new opportunities that can increase local participation in the tourism industry are still very small. This research attempts to fill this gap by exploring the tourism industry in Labuan Bajo, West Manggarai, East Nusa Tenggara. By identifying the capital possessed by local communities and opportunities that can arise through social capital. This research uses a qualitative approach type with case study research. In this study found the low level of capital owned by local communities that hinder their participation in the tourism industry, and how social capital can play its role to enhance the role of local communities in the tourism industry